A New Difference-Cum-Exponential Type Estimator of Finite Population Mean in Simple Random Sampling - Shabbir, Javid; Haq, Abdul; Gupta, Sat (Revista Colombiana de Estadística, 2014)
Auxiliary information is frequently used to improve the accuracy of the estimators when estimating the unknown population parameters. In this paper, we propose a new difference-cum-exponential type estimator for the finite population mean using auxiliary information in simple random sampling. The expressions for the bias and mean squared error of the proposed estimator are obtained under first order of approximation. It is shown theoretically, that the proposed estimator is always more efficient than the sample mean, ratio, product, regression and several other existing estimators considered here. An empirical study using 10 data sets is also conducted to validate the theoretical findings.